2022
DOI: 10.3389/fonc.2022.865865
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies and Outcomes for Intracranial Chondromas: A Retrospective Study of 17 Cases and Systematic Review

Abstract: ObjectiveTo improve the diagnosis and treatment of intracranial chondromas (ICDs) by discussing the clinical manifestations and imaging characteristics of ICDs, as well as surgical methods and treatment strategies.MethodsWe retrospectively analyzed 17 patients diagnosed with ICDs who underwent microsurgery or endoscopic transsphenoidal surgery at the Tangdu Hospital of Air Force Military Medical University and the Mianyang Central Hospital from January 2010 to November 2021. Clinical manifestations, imaging ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…One possible reason of this inconsistency may depend on definition of the extent of tumor resection. Although we defined GTR as more than 95% of tumor resected and defined STR as 80–95% of tumor resected in this study [ 17 , 18 ], majority of the reported investigations were stood on another standard as GTR as 100% and STR as more than 90% [ 37 40 ]. This may reflect the inconsistency between our study and previously reported statistical results.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason of this inconsistency may depend on definition of the extent of tumor resection. Although we defined GTR as more than 95% of tumor resected and defined STR as 80–95% of tumor resected in this study [ 17 , 18 ], majority of the reported investigations were stood on another standard as GTR as 100% and STR as more than 90% [ 37 40 ]. This may reflect the inconsistency between our study and previously reported statistical results.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Furthermore, other studies have reported that gross-total resection for a craniotomy was performed in 22.7% to 36.7% of affected cases, whereas EES was used in 58.8%. 18 , 19 This procedure has a few advantages. First, a chondroma is usually located in the epidural space, where it can be easily reached and removed without causing injury to surrounding structures such as arteries and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcoma shows a heterogeneous signal on T2-weighted images, with a “honeycomb” appearance after enhancement. However, there are no specific imaging findings in some intracranial chondrosarcomas, and they need to be differentiated from meningiomas, schwannoma, chordomas, and chondromas 7 , 12 14 . Based on the data from three hospitals in the past 12 years, CT showed that almost all the lesions had varying degrees of erosion and destruction, 15 cases with mixed high- and low-density shadows and 10 cases with irregular soft tissue shadows.…”
Section: Discussionmentioning
confidence: 99%
“…Chordoma, chondroma, and chondromyxoid fibroma are similar to chondrosarcoma in terms of location, imaging presentation, and pathological morphology. Compared with chondrosarcoma, chondroma is more differentiated and less likely to have binucleated cells; chordoma is more likely to immunohistochemically express CK and EMA; chondromyxoid fibroma is positive for S100, and positive to desmin and CD34 to varying degrees 7 , 34 , 38 . Among our 26 cases, 24 were chondrosarcoma grade I, two were chondrosarcoma grade II, and there was no mesenchymal chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation